1999
DOI: 10.1007/s004450050298
|View full text |Cite
|
Sign up to set email alerts
|

Pahoehoe toe dimensions, morphology, and branching relationships at Mauna Ulu, Kilauea Volcano, Hawai'i

Abstract: Pahoehoe toe dimensions, morphology, and branching relationships were analyzed in flows emplaced during 1972 at Mauna Ulu, a satellitic shield on the east rift zone of Kilauea Volcano, Hawai'i. In order to characterize regions within flow fields dominated by networks of pahoehoe toes, measurements of toe length, width, thickness, and orientation were completed for 445 toes at 13 sites. Variations in site characteristics, including slope, substrate, and position in the flow field allow an evaluation of the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Knowledge of the geographical position and direction of flows is used in hazard prediction (Trusdell 1995). Lava volumes can be estimated through either a combination of lava flow area with field-based lava flow thickness measurements (Shaw and Swanson 1970;Self et al 1997;Crown and Baloga 1999) or subtraction of pre-and post-eruptive digital elevation models (DEMs) (Rowland et al 2003;Lu et al 2004). These volumes can be used in magma supply models and time-series analyses of volcanic activity to further the understanding of eruption mechanisms (Burt et al 1994).…”
Section: Lava Flow Mappingmentioning
confidence: 99%
“…Knowledge of the geographical position and direction of flows is used in hazard prediction (Trusdell 1995). Lava volumes can be estimated through either a combination of lava flow area with field-based lava flow thickness measurements (Shaw and Swanson 1970;Self et al 1997;Crown and Baloga 1999) or subtraction of pre-and post-eruptive digital elevation models (DEMs) (Rowland et al 2003;Lu et al 2004). These volumes can be used in magma supply models and time-series analyses of volcanic activity to further the understanding of eruption mechanisms (Burt et al 1994).…”
Section: Lava Flow Mappingmentioning
confidence: 99%
“…Within a given local network these features may occur at high angles to the overall downflow direction defined by the path from the vent to the flow field terminus. The increased variability in flow orientation at smaller scales is due to the higher relative variability in topography at the scale of toes compared to channels [Crown et al, 1998. Earlier studies had suggested that pahoehoe flow eraplacement is fractal in nature based .on measurements of flow margins [Bruno et al, 1992[Bruno et al, , 1994].…”
mentioning
confidence: 99%
“…On the basis of measurements of sizes and orientations of individual pahoehoe features, recent analyses indicate that toes (tens to hundreds of centimeters) are gradational to small channels and sheets (1 to tens of meters) [Crown and 8aloga, 1999] and that emplacement processes within pahoehoe flows exhibit scale-dependent tendencies [Crown et al, 1998. Orientations of pahoehoe features (i.e., toes and channels) within the Mauna Ulu flow field display greater variability at small scales.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Crown and Baloga (1999) find that at the meter scale lava toes tend to be greater in length than width except on low slopes where toes tend to spread laterally and can have higher widths than lengths. Crown (1999, 2000) find that at the flow field scale (N10 m) flows do not consistently widen on shallower slopes across the Hawaiian plains but conclude that topographic influences control the final width of a lava flow.…”
Section: Discussionmentioning
confidence: 93%